MEDIA PAPAN MAGNET UNTUK MENINGKATKAN KEAKSARAAN AWAL PADA ANAK USIA 5-6 TAHUN DI TKIT AN NAJMA CIKARANG UTARA - Hidayati, Lala Nur; Syafrida, Rina; Riana, Nancy (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2024)
This research aims to find out whether the magnetic board media at TKIT An Najma North Cikarang can influence the early literacy of early childhood children aged 5-6 years. This research uses a classroom action research method that refers to Kemmis and Mc Taggart, whose process consists of planning, action, observation and reflection. This research started from pre-action, continued with cycle I then ended with cycle II. In cycle I there were seven meetings, while in cycle II there were six meetings. In this study, the subjects were 10 group B children consisting of 5 boys and 5 girls. The data analysis techniques used are quantitative and qualitative. Quantitative data analysis is to see the percentage of success, while qualitative data analysis is to explain the research results. As a result of this research, it has been proven that there is an improvement in children after using magnetic board media. The pre-action percentage results were 14%, cycle I 52% and cycle II 74%. Therefore, magnetic board media influences the early literacy of children aged 5-6 years at TKIT An Najma, North Cikarang.